2010
DOI: 10.1007/s12603-010-0098-6
|View full text |Cite
|
Sign up to set email alerts
|

BMI, life-style and psychological conditions in a sample of elderly italian men and women

Abstract: Men and women lead different lifestyles and have a different psychological status, with advancing age consequently stressing the need for healthy lifestyle programmes particularly in the case of overweight and obese elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Association of BMI/excess weight with socio-demographic variables found in our study are mostly in line with previous literature: BMI significantly decreased with age [ 29 ] (mBMI) and higher education [ 10 ] (systematic review), while risk for excess weight was higher for younger and less educated [ 35 ] (mBMI). Findings regarding sex - higher BMI and excess weight in men - are in line with the literature [ 24 ] (srBMI).…”
Section: Discussionsupporting
confidence: 92%
“…Association of BMI/excess weight with socio-demographic variables found in our study are mostly in line with previous literature: BMI significantly decreased with age [ 29 ] (mBMI) and higher education [ 10 ] (systematic review), while risk for excess weight was higher for younger and less educated [ 35 ] (mBMI). Findings regarding sex - higher BMI and excess weight in men - are in line with the literature [ 24 ] (srBMI).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies [20][21][22]24,27 classified body mass index as proposed by the World Health Organization. Although this classification does not take into account the body changes that accompany the aging process, it has been one of the most applied references in epidemiological studies worldwide 11,40,47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight articles excluded from the meta-analysis because they did not present OR as a measure of effect or because they reported more than one OR, four reported no association between sedentary behavior and overweight 31,32,36,49 , three reported an association 48,50,51 and one, which considered the results stratified by sex, reported a significant association only in women 52 . However, even if these studies were included in this meta-analysis, there would still be insufficient evidence of the relationship between longer exposure times to sedentary behavior and excess weight in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, physical activity in late life has been shown to be related specifically to depressive symptoms. For example, an Italian study revealed that lower rates of physical activity were associated with a greater extent of depression (Marcellini, et al, 2010). Another study of a slightly younger cohort, based upon data from the American Health and Retirement Study (HRS), found that a decrease from vigorous physical activity status was associated with increased odds for depressive symptoms among the women (but not among the men), as measured on the eight-item version of the Center for Epidemiologic Studies Depression Scale (Carroll, Blanck, Serdula, & Brown, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%